GLOBAL MARITIME FULCRUM, INDONESIA-CHINA GROWING RELATIONS, AND INDONESIA’S MIDDLEPOWERMANSHIP IN THE EAST ASIA REGION - Nanto Sriyanto (Jurnal Kajian Wilayah, 2018)
The relation between Indonesia and China sparks a new era by the signing of a strategic partnership agreement in 2005. The signing of strategic partnership and similarities in infrastructure booming in both countries initiates the significant flow of capital and cooperation. Under the presidency of Joko Widodo, Indonesia’s program of domestic connectivity, which dubbed as Global Maritime Fulcrum (GMF), has opened more extensive opportunity for China to invest and build complementarities of her Belt and Road Initiatives (BRI). Despite the fact that two countries could move into a strategic partnership, other factors have hampered the relations between the two. Indonesia's foreign policy doctrine will not allow herself to become fully aligned with other great power politics in the region. Indonesia has been long pursued an international activism based on free and active doctrine and dynamic equilibrium. These doctrinal factors in another sense become the primary foundation of Indonesia's middlepowermanship foreign policy. The challenge in this case is the contradiction between economic and political interests that has forced Indonesia to balance between her political interests and economic interests. While growing relations with China could help Indonesia implement her strategic infrastructure development that leads to a better economic capability, the situation could erode her aspiration as middle power country (middlepowermanship). This article would like to find how Indonesia juggles between those interest without undermining her position and credibility as an emerging middle power. This article proposes that even though domestic politics plays important role in fostering Indonesia position as middle power countries, at the same time Indonesia needs to strengthen her relations towards other countries and especially manage the centrality of ASEAN in the region to secure principle of dynamic equilibrium and the role of bridge builder.  Keywords: Global Maritime Fulcrum, middlepowermanship, dynamic equilibrium, bridge builder, down to earth diplomacy AbstrakHubungan Indonesia dengan Tiongkok memulai babak baru dengan penandatanganan kemitraan strategis pada tahun 2005. Penandatanganan tersebut dan kesamaan pada kebangkitan pembangunan infrastruktur di kedua negara mendorong peningkatan arus modal dan kerjasama. Di bawah kepemimpinan Presiden Joko Widodo yang mengusung program Global Maritime Fulcrum (GMF) dengan tujuan membangun konektifitas domestik, telah membuka peluang kerjasama bagi Tiongkok untuk menanamkan modal dan membangun kerjasama yang saling melengkapi dengan program Belt Road Initiatives (BRI). Meskipun peluang besar terbuka bagi kedua pihak, masih terdapat ganjalan bagi terbangunnya kerjasama yang lebih mendalam. Prinsip politik luar negeri Indonesia tidak memungkinkan Indonesia untuk sepenuhnya menggantungkan atau beraliansi dengan kekuatan besar di kawasan ataupun global. Indonesia sendiri telah lama menjalankan aktifisme internasional yang berdasarkan prinsip bebas aktif dan keseimbangan dinamis. Prinsip-prinsip tersebut menjadi dasar rujukan bagi middlepowermanshipdalam politik luar negeri Indonesia. Tantangannya dalam hal ini adalah bagaimana upaya Indonesia menyeimbangkan antara kepentingan politik dan ekonominya. Perkembangan hubungan ekonomi dengan Tiongkok dapat membantu Indonesia melaksanakan pembangunan infrastruktur strategis yang akan berdampak pada peningkatan kapabilitas ekonomi. Namun begitu, kedekatan yang tidak terimbangi akan dapat mengganggu politik luar negerinya sebagai kekuatan negara menengah (middlepowermanship). Artikel ini bertujuan mengetahui bagaimana Indonesia mengimbangi beragam kepentingan tersebut tanpa mengganggu posisi dan kredibilitasnya sebagai negara kekuatan menengah. Artikel ini berpendapat bahwa tanpa mengabaikan peranan faktor domestik, pada saat yang bersamaan Indonesia perlu membangun jalinan kerjasama dengan negara lain, terutama yang sejalan dengan penguatan sentralitas ASEAN demi perlindungan prinsip keseimbangan dinamis dan peranannya sebagai penjembatan di antara kekuatan besar.Kata Kunci: Global Maritime Fulcrum, middlepowermanship, keseimbangan dinamis, penjembatan, diplomasi membumi